Tabarru’ taste: a centralized hub for unifying shariah compliant efforts to alleviate poverty through food redistribution - Bohari, Najwatul Nadhirah; Mohamad Zamri, Nur Qurratuain Mardhiah; Mohammad Hatta, Mohammad Firdaus; Mohd Ishar, Nor Irvoni (Faculty of Business and Management, 2025)
Tabarru' Taste addresses food waste and hunger through a Shariah compliant approach, blending Islamic financial principles such as Tabarru', Waqf, Takaful, and Wakalah. The platform partners with grocery stores, small businesses, NGOs, and government agencies to collect and redistribute surplus food, reducing waste while providing for those in need. It actively promotes corporate social responsibility by offering incentives like awards, tax benefits, and recognition to participating SMEs, which in turn enhances their reputation and financial stability. The platform's foundation, rooted in Islamic values, makes it especially appealing in Muslim-majority regions, setting it apart in a competitive market. Environmental sustainability is central, with a focus on reducing landfill waste and greenhouse gas emissions through effective food redistribution. The platform encourages community involvement through donations and crowdfunding, fostering a culture of shared responsibility and unity. scalable and comprehensive model addresses immediate food security challenges and contributes to long-term community wellbeing and environmental sustainability.